Direct Sensing of Total Acidity by Chronopotentiometric Flash Titrations at Polymer Membrane Ion-Selective Electrodes - Gemene, K.; Bakker, Eric (American Chemical Society, 2008)
Polymer membrane ion-selective electrodes containing lipophilic ionophores are traditionally interrogated by zero current potentiometry, which, ideally, gives information on the sample activity of ionic species. It is shown here that a discrete cathodic current pulse across an H+- selective polymeric membrane doped with the ionophore ETH 5294 may be used for the chronopotentiometric detection of pH in well-buffered samples. However, a reduction in the buffer capacity leads to large deviations from the expected Nernstian response slope. This is explained by the local depletion of hydrogen ions at the sample-membrane interface as a result of the galvanostatically imposed ion flux in direction of the membrane. This depletion is found to be a function of the total acidity of the sample and can be directly monitored chronopotentiometrically in a flash titration experiment. The subsequent application of a baseline potential pulse reverses the extraction process of the current pulse, allowing one to interrogate the sample with minimal perturbation. In one protocol, total acidity is found to be proportional to the magnitude of applied current at the flash titration end point. More conveniently, the square root of the flash titration end point time observed at a fixed applied current is a linear function of the total acid concentration. This suggests that it is possible to perform rapid localized pH titrations at ion-selective electrodes without the need for volumetric titrimetry. The technique is explored here foracetic acid, MES and citric acid with promising results. Polymeric membrane electrodes based on poly(vinyl chloride) plasticized with o-nitrophenyl octyl ether in a 1:2 mass ratio may be used for the detection of acids of up to ca. 1 mM concentration, with flash titration times on the order of a few seconds. Possible limitations of the technique are discussed, including variations of the aciddiffusion coefficients and influence of electrical migration.